Asymptotical analysis of maxima with a random number of component variables - Aksomaitis, Algimantas (Lietuvos matematikos rinkinys, 1999)
Estimates of the convergence rate in the transference theorem are presented. They generalize and make more precise results obtained in [2] and [3].